STATISTICAL ASSESSMENT OF THE DEMOGRAPHIC SITUATION IN UZBEKISTAN - Khusinov Ibragim Ismailovich; Kuvvatov Golibjon Bakhtiyor ugli; Imamova Nasiba Muzafarovna (PT ANTIS International Publisher, 2024)
The article provides conclusions and suggestions for resolving possible problems arising as a result of a statistical assessment of factors affecting the current state of population growth in Uzbekistan.